RESOURCE USE EFFICIENCY AND ECONOMIES OF SCALE IN MAIZE FARMING: EVIDENCE FROM ONDO STATE, NIGERIA - Akinyemi , Oluwaseun Michael; Fasoranti , Temidayo James (Ayden Journal of Agriculture and Allied Studies, 2025)
One of the challenges facing smallholder farmers in Nigeria is the inefficiency of resource use. The study was therefore conducted to investigate resource use efficiency and return to scale in maize production in the study area. Data were collected from randomly selected 120 maize farmers using a self-designed structure questionnaire in the study area. Data were analysed with the aid of descriptive statistics and Cobb-Douglas production function. Findings showed resources in the area were inefficiently allocated. Seed, labour and fertilizer were under-utilized while farm size and pesticides were overutilized. The returns to scale analysis showed that maize farmers in the area were in irrational stage one of the production curve. The study concluded that maize farmers in the area can increase production by employing more of productive resources